Meeting the challenges of sustainable democracy in Nigeria - Ajakaiye, David Olusanya Ishola; Roberts, F. O. Nyemutu; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research (NISER), 2002)
An analysis of sustainable democracy in Nigeria.
Papers presented at a seminar held in May 2001 in Ibadan.
Includes bibliographical references and index.
oif 10/03/15
Loan
Keywords: Democracy; Democratization; Political culture; Nigeria